Cloud based platforms, tools and services - A. V. Damniskaya (Academy of Cognitive and Natural Sciences, 2017)
Research goals: to determine the impact of cloud platforms, equipment and services at the modern state of ICT development. Research objectives: to determine the place and role, pros and cons of the cloud technologies, relevance of their use by the user today. Object of research: cloud services and their characteristics. Subject of research: the use of cloud based technologies, their products and services they can provide. Research methods used: analysis of cloud platforms, statistical data, and scientific publications. Results of the research: based on statistical data confirmed the relevance of using cloud applications. Analyzed the characteristics and scientific publication and proved the influence of cloud technologies on future IT-professionals competences. The main conclusions and recommendations: the use of cloud technology is more affordable, manageable and practical way of data management, which is not require local infrastructure; knowledge and skills related to cloud services is a basis competences of future IT professionals.